2008
DOI: 10.1111/j.1438-8677.2008.00098.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth and photosynthetic responses to zinc stress of an invasive cordgrass, Spartina densiflora

Abstract: Spartina densiflora Brongn. is found in coastal marshes of southwest Spain, growing over sediments containing 100-4800 ppm Zn. A glasshouse experiment was designed to investigate the effect of Zn from 0 to 100 mmol.l(-1) on the growth and photosynthetic apparatus of S. densiflora, by measuring relative growth rate, leaf elongation rate, number of tillers, height of tillers, chlorophyll fluorescence parameters, gas exchange and photosynthetic pigment concentrations. We also determined total ash, Zn, calcium, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(37 citation statements)
references
References 44 publications
6
31
0
Order By: Relevance
“…Tavori et al (2004) also reported that NaCl concentration in high amounts decreased Ca accumulation in the stem and the leaves of chickpea. Mateos-Naranjo et al (2008) found that Zn reduced the tissue Ca concentration of S. densiflora.…”
Section: Figmentioning
confidence: 92%
“…Tavori et al (2004) also reported that NaCl concentration in high amounts decreased Ca accumulation in the stem and the leaves of chickpea. Mateos-Naranjo et al (2008) found that Zn reduced the tissue Ca concentration of S. densiflora.…”
Section: Figmentioning
confidence: 92%
“…During this period the entire solutions were changed on a 5 d basis. Zn and NaCl concentrations were chosen to cover variations recorded by Mateos-Naranjo et al (2008 a and b , respectively) in the salt marshes of Odiel River where S. densiflora occurs.…”
Section: Methodsmentioning
confidence: 99%
“…Cambrollé et al (2008) found that heavy metals (including Zn) accumulated at different rates in S. densiflora tissues and around its roots, concluding that these species could be used for phytoremediation and phytostabilization of estuarine sediments. Mateos-Naranjo et al (2008 a ) studied the effect of Zn on the growth and photosynthetic apparatus of S. densiflora in a glasshouse experiment, but no attention was paid to the interaction with salt.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescence parameters were determined synchronously with the gas exchange measurements in the field using a portable pulsemodulated fluorometer (FMS-2, Hansatech, England) under natural conditions according to Mateos-Naranjo et al (2008). Tested leaves were kept in the dark for 30 min before measurement.…”
Section: Measurement Of Leaf Chlorophyll Fluorescencementioning
confidence: 99%